The impact of social media in the promotion of reading and book sales in Latin America between 2010-2020 - Giuria Farias, Camila (2021)
The booktube and bookstagram subcommunities on social networks have had a great impact on reading habits and book-related businesses in Latin America in the last decade. This paper studies the influence of the social networks YouTube and Instagram on the promotion of reading and book sales, as well as the causes and consequences of this phenomenon. The communication facilities of each social network due to the multimedia capabilities of their platforms determine the success of each one in different aspects, since Instagram is ideal for online sales marketing, and YouTube fulfills persuasive purposes that manage to promote reading habits. This article concludes that, of the two platforms presented, YouTube and the booktube community have had a great influence in the promotion of reading due to the ease with which a connection link can be created; and Instagram had a greater success in online sales and book fairs, due to the ease of sending a concise message.